Activity of xanthine oxidase in plasma correlates with indices of insulin resistance and liver dysfunction in patients with type 2 diabetes mellitus and metabolic syndrome: A pilot exploratory study. Issue 1 (7th July 2018) - Sunagawa, Sumito; Shirakura, Takashi; Hokama, Noboru; Kozuka, Chisayo; Yonamine, Masato; Namba, Toyotaka; Morishima, Satoko; Nakachi, Sawako; Nishi, Yukiko; Ikema, Tomomi; Okamoto, Shiki; Matsui, Chieko; et al.
Abstract: Aims/Introduction: There is controversy as to whether hyperuricemia is an independent risk factor for cardiometabolic diseases. The serum level of uric acid is affected by a wide variety of factors involved in its production and excretion. In contrast, evidence has accumulated that locally‐ and systemically‐activated xanthine oxidase (XO), a rate‐limiting enzyme for production of uric acid, is linked to metabolic derangement in humans and rodents. We therefore explored the clinical implication of plasma XO activity in patients with type 2 diabetes mellitus and metabolic syndrome (MetS). Materials and Methods: We enrolled 60 patients with type 2 diabetes mellitus and MetS. MetS was defined according to the 2005 International Diabetes Federation guidelines. Plasma XO activity was measured by highly‐sensitive fluorometric assay measuring the conversion of pterin to isoxanthopterin, and explored associations between the value of plasma XO activity and metabolic parameters. Results: The value of plasma XO activity was correlated with indices of insulin resistance and the level of circulating liver transaminases. In contrast, the level of serum uric acid was not correlated with indices of insulin resistance. The value of plasma XO activity was not correlated with the serum uric acid level. Conclusions: Plasma XO activity correlates with indices of insulin resistance and liver dysfunction in Japanese patients with type 2 diabetes mellitus and MetS. Through assessing the plasma XO activity, patients showing normal levels of serum uric acid with higher activity of XO can be screened, thereby possibly providing a clue to uncovering metabolic risks in type 2 diabetes mellitus and MetS patients. Abstract : In 50 patients with T2DM and MetS, value of plasma XO activity was correlated with indices of insulin resistance and levels of circulating transaminases. Value of plasma XO activity was not correlated with serum uric acid level in these patients. Level of serum uric acid was not correlated with indices of insulin resistance in these patients. Assessment of plasma XO activity may provide a novel clue to uncover hidden risks for T2DM and endothelial dysfunction in humans.